2020
DOI: 10.1164/rccm.2020c1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of COVID-19 Disease

Abstract: Biology ■ SARS-CoV-2 is single-stranded RNA, enveloped virus that likely spread to humans from a zoonotic source, possibly bats or pangolins 1. ■ It is believed to spread from person to person via respiratory droplet nuclei 2. ■ Other routes of infection (e.g. contact, enteric) are possible as the virus can persist on surfaces and is shed in feces, but it is unclear if these are significant means of spread. 2,3 ■ There is evidence of transmission by asymptomatic individuals 4. ■ The virus binds to the ACE2 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 1 publication
2
54
0
5
Order By: Relevance
“…This was also supported by the laboratory abnormalities found in our patient, which were lymphopenia, leucopenia, thrombocytopenia, elevated creatinine, AST and ALT, and hypoxemia from blood gas analysis, and also pneumonia by chest X-ray and CT scan findings (bilateral, peripheral, patchy opacities on chest X-ray and bilateral ground-glass opacities, crazy paving, and multifocal consolidation from chest CT scan) that suggest high probable for COVID-19 infection. It is suggested that findings from chest CT scans usually peak around 9-13 days [6,7]. WHO criteria for confirmed COVID-19 was based on the detection of unique sequences of virus SARS-CoV-2 RNA by nucleic acid amplification tests such as realtime RT-PCR and needed at least two positive results [8].…”
Section: Discussionmentioning
confidence: 99%
“…This was also supported by the laboratory abnormalities found in our patient, which were lymphopenia, leucopenia, thrombocytopenia, elevated creatinine, AST and ALT, and hypoxemia from blood gas analysis, and also pneumonia by chest X-ray and CT scan findings (bilateral, peripheral, patchy opacities on chest X-ray and bilateral ground-glass opacities, crazy paving, and multifocal consolidation from chest CT scan) that suggest high probable for COVID-19 infection. It is suggested that findings from chest CT scans usually peak around 9-13 days [6,7]. WHO criteria for confirmed COVID-19 was based on the detection of unique sequences of virus SARS-CoV-2 RNA by nucleic acid amplification tests such as realtime RT-PCR and needed at least two positive results [8].…”
Section: Discussionmentioning
confidence: 99%
“…And the general centers systematically helped to prevent community spread across the country. Previous studies showed the necessity to prevent spread of COVID-19 in areas with high population density through control measures [17][18][19]. For this reason, South Korea appeared to distribute the general and DT screening centers in Seoul, Gyeonggi-do, and six large cities with high population density.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used drugs are antibiotics, and the rational use of antibiotics may be helpful for the prognosis. For severe patients, clinical guidelines recommend experiential antibiotics [19,20]. For others, it remains controversial to decide when to start using antibiotics.…”
Section: Discussionmentioning
confidence: 99%